THE FUNDRAISING STRATEGY OF ZAKAT IN NATIONAL ZAKAT AGENCY OF EAST JAVA - Deta Brilyanti Asanjaya; Sri Abidah Suryaningsih (Journal of Economics and Business Aseanomics (JEBA), 2021)
This study aimed to gain strategy and zakat fundraising strategy evaluation applied at National Zakat Agency of East Java Province. This study used qualitative approach by primary and secondary data collecting. Interviewers of this study who came from different background, which are National Zakat Agency of East Java Province employees and academicians. Finding of this study shows there are three strategies at National Zakat Agency of East Java Province, the strategy is to build an image of an independent and professional institution, creates standardize the working mechanism of the zakat management organization, and build a muzaki and mustahik data base centrally . This study also informs socialization become main reason to increase zakat fundraising at National Zakat Agency of East Java Province.